Recent Advances and Promises in Nitrile Hydratase: From Mechanism to Industrial Applications - Cheng, Zhongyi; Xia, Yuanyuan; Zhou, Zhemin (Frontiers in Bioengineering and Biotechnology, 2020)
Nitrile hydratase (NHase, EC 4.2.1.84) is one type of metalloenzyme participating in the biotransformation of nitriles into amides. Given its catalytic specificity in amide production and eco-friendliness, NHase has overwhelmed its chemical counterpart during the past few decades. However, unclear catalytic mechanism, low thermostablity, and narrow substrate specificity limit the further application of NHase. During the past few years, numerous studies on the theoretical and industrial aspects of NHase have advanced the development of this green catalyst. This review critically focuses on NHase research from recent years, including the natural distribution, gene types, posttranslational modifications, expression, proposed catalytic mechanism, biochemical properties and potential applications of NHase. The developments of NHase described here are not only useful for further application of NHase, but also beneficial for the development of the fields of biocatalysis and biotransformation.